FAKTOR YANG MEMPENGARUHI KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS REJOSARI PEKANBARU - Hartati, Susi; Nurazila, Nurazila (Jurnal Endurance, 2018)
Diarrheal is still a global problem with  high degree of morbidity and mortality in many countries, especially in developing countries, as well as  one of  high rates s of  morbidity and mortality in the world. This study aims to examine the factors that affect the incidence of diarrhea in infants at area health center Rejosari Year in 2017. This type of  research quantitative  with cross sectional design with chi square test. Place of research at  the health center Rejosari  Pekanbaru  on 01 to 13 May 2017. The Sampling technique using  consecutive sampling technique, population in this study amounted to 379 people and a sample of 195 people. Primary data collection with questionnaire. The processing data is SPSS includes editing, coding, sorting, entry, scoring and tabulating. The analysis is univariate and bivariate. The result of research there is correlation factor between independent variable and dependent variable which means Ha accepted and Ho rejected with p-value <α = 0,05. education p-value = 0,000, knowledge p-value = 0,000, handwashing behavior p-value = 0,000. So it is concluded that there is a factor relationship that affects the incidence of diarrhea in infants in the work area of health center Rejosari Pekanbaru in 2017Penyakit diare masih menjadi masalah global dengan derajat kesakitan dan kematian yang tinggi di berbagai negara terutama di negara berkembang, dan juga sebagai salah satu penyebab utama tingginya angka kesakitan dan kematian anak di dunia. Penelitian ini bertujuan untuk meneliti faktor-faktor yang mempengaruhi kejadian diare pada balita di Wilayah Kerja Puskesmas Rejosari Tahun 2017. Jenis penelitian kuantitatif dengan desain cross sectional dengan uji Chi square. Tempat penelitian di Puskesmas Rejosari Pekanbaru pada tanggal 01 hingga 13 Mei tahun 2017. Teknik sampling consecutive sampling, populasi dalam penelitian ini berjumlah 379 orang dan sampel berjumlah 195 orang. Pengumpulan data primer dengan lembar kuesioner. Pengolahan data SPSS meliputi editing, coding, sorting, entry, skoring dan tabulating. Analisa data adalah univariat dan bivariat. Hasil penelitian terdapat hubungan faktor antara variabel independen dan variabel dependen yang artinya Ha diterima dan Ho ditolak dengan nilai p-value<α=0,05.  pendidikan p-value= 0,000, pengetahuan p-value= 0,000, perilaku mencuci tangan p-value= 0,000. Maka disimpulkan terdapat hubungan faktor yang mempengaruhi kejadian diare pada balita di Wilayah Kerja Puskesmas Rejosari Pekanbaru tahun 2017.